Pinocchio Coin: Building Zerocoin from a Succinct Pairing-based Proof System - Danezis, George; Fournet, Cédric; Kohlweiss, Markulf; Parno, Bryan (Workshop on Language Support for Privacy Enhancing Technologies, 2013)
Bitcoin is the first widely adopted distributed e-cash system and Zerocoin is a recent proposal to extend Bitcoin with anonymous transactions. The original Zerocoin protocol relies heavily on the Strong RSA assumption and double-discrete logarithm proofs, long-standing techniques with known performance restrictions. We show a variant of the Zerocoin protocol using instead elliptic curves and bilinear pairings. The proof system makes use of modern techniques based on quadratic arithmetic programs resulting in smaller proofs and quicker verification. We remark on several extensions to Zerocoin that are en-abled by the general-purpose nature of these techniques